Mi’kmaq and Maliseet Tom Longboat Award Recipients’ Experiences in Sport in the Maritimes - Lodge, Vanessa (Université d'Ottawa / University of Ottawa, 2012)
This thesis employs postcolonial theory, a case study methodology, semi-structured interviews, and archival research to understand Mi’kmaq and Maliseet peoples’ sporting experiences in the Maritimes region of Canada. Two publishable papers comprise this thesis. The first paper analyzes the obstacles the participants faced and the positive experiences they had in sport. The second paper examines the ways in which the concept of “difference” was reproduced and challenged through the participants’ involvement in mainstream and all-Native sporting environments. Together, these papers bring much needed scholarly attention to Mi’kmaq and Maliseet peoples’ involvement in sport in the Maritimes, while they also make a contribution to the existing body of literature concerning Aboriginal peoples’ sport participation in Canada.